Gaudi in Psychology (in Russian) - ПетровскийВадим Артурович (Psychology. Journal of the Higher School of Economics, 2016)
There are two path-breakers, two thinkers, one in science and the other in art – Vladimir Lefevr and Antonio Gaudi – that have a deep personal kinship: out-of-the-box decisions, diverse competences, incisive intuitions, aesthetics of thought, bold imagination – they have all these “in common”. An architect of a ground-breaking reflexive theory, V.A. Lefevr built a bridge between two realiae – on this and on the other side of a human self. The theoreticians-predecessors dealt with transitions “inner – outer”. But it is Lefevr, who built a model, which not only describes, but also predicts the pattern of transitions between consciousness and behavior. The author of this article offers some interpretations that will allow comprehending the elements of mathematical analysis that Lefevr uses, deriving their psychological meaning (as “physical meaning” of mathematical symbols is revealed in natural sciences). From this standpoint the article interprets intrapersonal transactions between Berne’s Parent, Adult and Child in the moments of decision-making; facts of disagreement of the J. Atkinson’s model of “decision-making” with the empirical data (and offers the model that corrects non-conformances); phenomena of active inadaptability (“altruistic risk”, statement of the “above-situational” tasks in cognition, Oedipus paradox); “subjective assemblage points” in the inner space of personality, which help realize its goals in the anticipated results; phenomena of inner communications “me – the other me”, generated by means of recursion, etc.